2021
DOI: 10.1136/lupus-2021-000569
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of NEU1 as a candidate renal biomarker for proliferative lupus nephritis chronicity

Abstract: ObjectiveProteomic approach was applied to identify candidate biomarkers of chronicity in patients with proliferative lupus nephritis (LN), and their clinicopathological significance and prognostic values were investigated.MethodsThis study recruited 10 patients with proliferative LN and 6 normal controls (NCs) with proteomic data to compare protein expression profiles, 58 patients with proliferative LN and 10 NCs to verify proteomic data by immunohistochemistry, and 14 patients with proliferative LN with urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Pathways include metabolism [55], neutrophil degranulation [56], metabolism of lipids [57], immune system [58], metabolism of proteins [59] and TP53 [60] regulates metabolic genes were linked with progression of T1DM. KDM7A [61], LMNA (lamin A/C) [62], PFKFB3 [63], NEU1 [64], DUSP22 [65], ADORA2B [66], CRTC2 [67], GRN (granulin precursor) [68], CTSD (cathepsin D) [69], IGFBP4 [70], SMYD2 [71], OSM (oncostatin M) [72], INVS (inversin) [73], ANKFY1 [74], SEMA4D [75], PPM1A [76], IFNG (interferon gamma) [77], CTBP1 [78], ATP6 [79], COX2 [80], RPS19 [81], COX1 [82] and TLK1 [83] are potential biomarkers for the detection and prognosis of renal diseases. A previous study reported that LXN (latexin) [84], LMNA (lamin A/C) [85], PFKFB3 [86], NEU1 [87], TBK1 [88], GRN (granulin precursor) [89], CTSD (cathepsin D) [90], ACADS (acyl-CoA dehydrogenase short chain) [91], IRF7 [92], S1PR1 [93], ZAP70 [94], IDH1 [95], IL15 [96], PIK3R1 [97], OSM (oncostatin M) [98], SOCS3 [99], USP21 [100], CEP19 [101], KDM2A [102], TP53 [103], BRD2 [104], ATP6 [105], BRD4 [106], COX2 [107], RPS6 [108], ND2 [109], CYTB (cytochrome b) [110] and COX1 [111] are altered expressed in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Pathways include metabolism [55], neutrophil degranulation [56], metabolism of lipids [57], immune system [58], metabolism of proteins [59] and TP53 [60] regulates metabolic genes were linked with progression of T1DM. KDM7A [61], LMNA (lamin A/C) [62], PFKFB3 [63], NEU1 [64], DUSP22 [65], ADORA2B [66], CRTC2 [67], GRN (granulin precursor) [68], CTSD (cathepsin D) [69], IGFBP4 [70], SMYD2 [71], OSM (oncostatin M) [72], INVS (inversin) [73], ANKFY1 [74], SEMA4D [75], PPM1A [76], IFNG (interferon gamma) [77], CTBP1 [78], ATP6 [79], COX2 [80], RPS19 [81], COX1 [82] and TLK1 [83] are potential biomarkers for the detection and prognosis of renal diseases. A previous study reported that LXN (latexin) [84], LMNA (lamin A/C) [85], PFKFB3 [86], NEU1 [87], TBK1 [88], GRN (granulin precursor) [89], CTSD (cathepsin D) [90], ACADS (acyl-CoA dehydrogenase short chain) [91], IRF7 [92], S1PR1 [93], ZAP70 [94], IDH1 [95], IL15 [96], PIK3R1 [97], OSM (oncostatin M) [98], SOCS3 [99], USP21 [100], CEP19 [101], KDM2A [102], TP53 [103], BRD2 [104], ATP6 [105], BRD4 [106], COX2 [107], RPS6 [108], ND2 [109], CYTB (cytochrome b) [110] and COX1 [111] are altered expressed in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…These components are, therefore, potential biomarkers for LN diagnosis and monitoring (Table 2). [41][42][43][44][45][46][47] For example, variations in urinary sediment podocin and podocalyxin levels among LN patients emphasize the diagnostic value of podocyte components. 41…”
Section: Podocyte Markers As Diagnostic Tools For Lnmentioning
confidence: 99%
“…Urinary sediment podocin (used Pod) mRNA Associated with severe proliferative LN [41] Urinary supernatant podocalyxin protein Associated with subepithelial dense deposit LN Neuraminidase 1 Associated with pathological CI scores and renal outcomes in patients with proliferative LN [42] Podocyte-derived microparticles Positively correlated with increased proteinuria [43] Cmaf-inducing protein Be limited to nonproliferative forms and may define a specific pattern of podocyte injury in LN [44] Podocalyxin Urinary podocalyxin level significantly predicts the pathological impact of SLE on the kidney [45] Soluble urokinase plasminogen activator receptor Urine suPAR levels raised again in patients with a relapse of LN [46] S100 proteins Higher urine S100 levels are associated with increased LN activity in childhood-onset SLE [47] Abbreviations: CI, chronicity index; LN, lupus nephritis; mRNA, messenger RNA; SLE, systemic lupus erythematosus, suPAR, soluble urokinase plasminogen activator receptor. phosphorylation of nephrin in LN.…”
Section: Podocyte Component Function Referencesmentioning
confidence: 99%
“…In human studies, proteomic analysis of renal tissues comparing patients with proliferative lupus nephritis vs . healthy controls revealed NEU1 as the greatest up-regulated protein of 48 identified proteins ( 341 ). NEU1 immunohistochemical staining and urinary excretion were significantly elevated in lupus nephritis patients compared with controls.…”
Section: Neus and Mucs In Autoimmune Diseasesmentioning
confidence: 99%